Obtaining and Characterization of Mesophilic Bacterial Consortia from Tropical Sludges Applied on Biohydrogen Production - Pachiega, Renan [UNESP]; Sakamoto, Isabel Kimiko; Varesche, Maria Bernadete; Hatanaka, Rafael Rodrigues [UNESP]; de Oliveira, José Eduardo [UNESP]; Maintinguer, Sandra Imaculada [UNESP] (Springer Nature, 2018)
The biohydrogen production from different tropical sludges of biologic treatment plants was investigated in anaerobic batch reactors fed with sucrose in concentrations similar to food wastewaters. The tropical sludges tested were: I—granular sludge from a upflow anaerobic sludge blanket (UASB) reactor treating brewery wastewater; II—facultative anaerobic sludge from sedimentation pond treating domestic sewage; III—granular sludge from UASB reactor treating domestic sewage. The anaerobic batch reactors fed with 2 g L−1 of sucrose at pH 5.5 and 37 °C showed higher production of H2 than all tropical sludges tested. The maximum yield was 2.0 mol H2 mol of sucrose−1. The intermediary products during fermentation were acetic and butyric acids. Therefore, the bioproduction probably followed both the acetic acid and butyric acid route. A wide diversity of hydrogen producing bacteria identified as Clostridium sp., Bacillus megaterium, Staphylococcus sp., Bacillus subtilis and Lactobacillus sp. was observed by phylogenetic analysis. Tropical sludges from biologic treatment plants can be applied on biohydrogen production.
Keywords: 16S RNA; Anaerobic bacteria; Clostridium; Denaturing gradient gel electrophoresis; Lactobacillus; Sucrose; TOGA gas analyzer